2002
DOI: 10.1302/0301-620x.84b7.13032
|View full text |Cite
|
Sign up to set email alerts
|

Hemicortical allograft reconstruction after resection of low-grade malignant bone tumours

Abstract: Low-grade surface tumours of bone may theoretically be treated by hemicortical resection, retaining part of the circumference of the cortex. An inlay allograft may be used to reconstruct the defect. Since 1988 we have performed 22 hemicortical procedures in selected patients with low-grade parosteal osteosarcoma (6), peripheral chondrosarcoma (6) and adamantinoma (10). Restricted medullary involvement was not a contraindication for this procedure. There was no evidence of local recurrence or distant metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…2), which have presumably higher consolidation rates due to the larger contact area as well as the lower extent of soft tissue dissection [7]. Similar to our results, comparable studies on hemicortical reconstructions with auto- or allografts following tumour resection showed lower non-union rates of only 0–7% [7, 3336]. …”
Section: Discussionsupporting
confidence: 86%
“…2), which have presumably higher consolidation rates due to the larger contact area as well as the lower extent of soft tissue dissection [7]. Similar to our results, comparable studies on hemicortical reconstructions with auto- or allografts following tumour resection showed lower non-union rates of only 0–7% [7, 3336]. …”
Section: Discussionsupporting
confidence: 86%
“…In the literature, six cases of fractures of the remaining hemi cortex and two cases of minor subcortical resorption of the graft in the report of 22 cases of hemicortical allograft reconstruction after resection of low-grade malignant bone tumors are described. Reconstruction with allograft was not judges indicated when large resection was done, as in our case [12]. We used cement and plate (LISS-SINTHES) to reconstruct the bone defect, and we think that this is a new valid and alternative technique when it is not possible to use allograft and to prevent allograft complications such as fractures and bone resorption.…”
Section: Discussionmentioning
confidence: 94%
“…In this case, the minimal focal spread into the medullar canal did not prevent to obtain a wide surgical margin. This seems possible because invasions usually involve less than 25% of the medullar canal [7, 12]. Marginal excision usually results in hemicortical defect of the bone usually reconstructed with allograft [10].…”
Section: Discussionmentioning
confidence: 99%
“…Deijkers et al (2002) described 22 patients with low-grade malignant bone tumors who underwent hemicortical resections. A fracture of the remaining hemicortex occurred in 6 patients: in 3 patients during the operation and in 3 others shortly afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the technique to be a safe alternative to larger segmental resections for low-grade chondrosarcoma (Deijkers et al 2002), pareostal osteosarcoma (Lewis et al 2000, Pezzillo et al 2008), and adamantinoma (Agarwal et al 2007). However, several complications have been reported with this resection and reconstruction, the most important being fractures of the host bone, inadequate margins, and infection.…”
mentioning
confidence: 99%